Physical and physiological characteristics of male Zimbabwean league basketball players - Makaza, D.; Amusa, L. O.; Goon, D. T.; Gundani, M. P.; Mugandani, S. C. (Medicina dello Sport, 2012)
Aim. Information on physical and physiological performance characteristics of players is important to both coaches and players for training and competition planning. The purpose of this study was to investigate the physical and physiological characteristics of male Zimbabwean League basketball players. Methods. Twenty six players (6 point guards, 7 shooting guards, 9 forwards and 4 centres) participated in the study. They were measured for height, weight, muscular strength (leg, back, handgrip right and left), leg power (vertical jump), speed (20m sprint), agility (SEMO agility test), flexibility (trunk flexion, trunk extension and shoulder extension), local muscular endurance (upper body, abdominals and lower body), hand and eye coordination and maximal aerobic power (multistage shuttle run). Anthropometric variables were measured using the standardized procedures of the International Society for the Advancement of Kinanthropometry (ISAK). Physical and physiological measurements were taken following standard protocols. Descriptive and comparative analysis was done using SPSS version 17.0. Results. The results indicated mass of 68.3±9.7 kg, height 1.79±0.07 m, leg strength 92.3±31.7 kg, back strength 111.0±24.7 kg, relative strength 4.5±0.8 kg, leg power 108.1±13 kg, speed 3.1±1.1 s, trunk flexion 30.7±7.3 cm, trunk extension 35.2±9.7 cm, shoulder extension 29.3±14.2 cm, hand and eye coordination 27±3, agility 12.3±0.9 s, muscle endurance (push ups 30±10, sit ups 39±6, burpees 16±2 and aerobic capacity 45±3.5 mL/kg/min. The average values for all variables across categories of playing positions were found not to be significantly different at P=0.05 except for height F (3, 22) =13.15, PConclusion. These findings suggest that position specific training does not occur in the basketball league. The players were found to be lighter and shorter than players elsewhere. Generally, the physical and physiological characteristics of the basketball players ranged between average to poor when compared to players elsewhere.